Arthrobacter ulcerisalmonis sp. nov., isolated from an ulcer of a farmed Atlantic salmon (Salmo salar), and emended description of the genus Arthrobacter sensu lato. Issue 3 (27th January 2020) - Kämpfer, Peter; Busse, Hans-Jürgen; Schumann, Peter; Criscuolo, Alexis; Clermont, Dominique; Irgang, Rute; Poblete-Morales, Matías; Glaeser, Stefanie P.; Avendaño-Herrera, Ruben
Abstract : A Gram-stain positive, pleomorphic, oxidase-negative, non-motile isolate from the ulcer of a farmed Atlantic salmon ( Salmo salar ), designated strain T11b T, was subjected to a comprehensive taxonomic investigation. A comparative analysis of the 16S rRNA gene sequence showed highest similarities to the type strains of Pseudarthrobacter siccitolerans (98.1 %) and Arthrobacter methylotrophus and Pseudarthrobacter phenanthrenivorans (both 98.0 %). The highest ANI value observed between the assembled genome of T11b T and the publicly available Pseudarthrobacter and Arthrobacter type strain genomes were 81.15 and 80.99 %, respectively. The major respiratory quinone was menaquinone MK-9(H2 ). The polyamine pattern contained predominantly spermidine. The polar lipid profile consisted of the major lipids diphosphatidylglycerol, phosphatidylglycerol, monogalactosyl-diacylglycerol and dimannosylglyceride. Minor amouts of trimannosyldiacylglycerol and phosphatidylinositol were also detected. The peptidoglycan was of the type A3α l -Lys–l -Ser–l -Thr–l -Ala (A11.23). In the fatty acid profile, anteiso and iso branched fatty acids predominated (anteiso C15 : 0, iso C16 : 0, anteiso C17 : 0 ). Moderate to low DNA–DNA similarities, physiological traits as well as unique traits in the fatty acid pattern distinguished strain T11b T from the next related species. All these data point to the fact that strain T11b T represents a novel species of the genus Arthrobacter for which we propose the name Arthrobacter ulcerisalmonis sp. nov. The type strain is T11b T (=CIP 111621 T =CCM 8854 T =LMG 30632 T =DSM 107127 T ).